KONTRADIKSI ANTI TAKWIL ABDUL AZZ BIN ABDULLH BIN BZ: TAFSIR TERHADAP ANTROPOMORPHISME - Mujahid, Ahmad (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2015)
In Quranic studies, the issues of Muhkam and Mutasyabbih verses always have been discussed, how to understandeach them. Interpreting mutasyabihat verses has been a need because many of them tell about theology in the context ofanthropomorphism. Almost all scholars tend to use takwil to interpret them, but Abdul Azz bin Abdullh bin Bzoffered the opposite method. He avoided takwil. In this study, this writing discusses how Ibn Bz understood mutasyabihatverses especially about anthropomorphism. As a conclusion, the researcher found that the anti-takwil is stated by IbnBz and his allies, in its practice was sometimes contradictory. To enrich this article, the writer will trace the genealogyof the thought of Ibn Bz and his dialectic with the understanding or other streams such as Mutazilah, Asyariyyahto Maturidiyah